2010
DOI: 10.11646/zootaxa.2705.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A review of the genus Dexia Meigen in the Palearctic and Oriental Regions (Diptera: Tachinidae)

Abstract: The Palearctic and Oriental species of the genus Dexia Meigen are revised. Thirty-one described species are recognized as valid, viz. D. atripes (Malloch), D. basifera Walker, D. bivittata Townsend, D. caldwelli Curran, D. divergens Walker, D. extendens Walker, D. flavida (Townsend), D. flavipes Coquillett, D. fraseri (Malloch), D. fulvifera Röder, D. fusiformis Walker, D. gilva Mesnil, D. hainanensis Zhang, D. lepida Wiedemann, D. longipennis (Townsend), D. longipes (Townsend), D. luzonensis (Townsend), D. ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The systematic order and nomenclature follow those of Herting and Dely-Draskovits 42 and O’Hara and Henderson 43 , and the genus level classification was based primarily on Tschorsnig and Richter 44 and Cerretti et al 45 All the tachinid specimens were identified to the species level with integration of the recent literature 27 , 43 , 44 , 46 53 .…”
Section: Methodsmentioning
confidence: 99%
“…The systematic order and nomenclature follow those of Herting and Dely-Draskovits 42 and O’Hara and Henderson 43 , and the genus level classification was based primarily on Tschorsnig and Richter 44 and Cerretti et al 45 All the tachinid specimens were identified to the species level with integration of the recent literature 27 , 43 , 44 , 46 53 .…”
Section: Methodsmentioning
confidence: 99%